Assessment of the inelastic structural response of building models that consider the combination of orthogonal seismic effects. (1st May 2021) - Mejía-Pérez, Daniel; Valdés-González, Jesús; De-la-Colina, Jaime
Highlights: Combination of horizontal orthogonal seismic effects on building models. Optimal percentages to combine the orthogonal seismic effects on buildings. Influence of incident angle in the behavior of inelastic building models. Total costs evaluation of inelastic building models. Abstract: For design purposes, the orthogonal seismic effects are combined using a percentage combination rule. The most common rules estimate the total structural response as the sum of 100% of the effects caused by one earthquake component acting along one direction of the structure plus a percentage α of the response caused by the orthogonal earthquake component acting along the perpendicular direction of the structure. Usually, values of α = 30% or 40% are specified. There is no clear consensus regarding the use of a specific value of α. In this paper, a comprehensive parametric study is presented to analyze the effects of using a particular value of α on both the ductility demands and the total cost of buildings. The aim of the study is to obtain optimal values of α to minimize the total cost of buildings considering the following variables: structure dynamic properties, earthquake angle of incidence (0–360°), reduction factor of design elastic forces (design ductility demand) (Q = 2 or 4) and type of soil (firm or soft). Values of α = 10%, 30%, 50%, 70% and 100% are analyzed. The studied models are idealized building structural models with several combinations of vibration periods along both model orthogonal directions. Combining all values of the studied variables, a total of 66, 600 different cases were designed and analyzed. Based on both the designs and the analysis nonlinear results, the total costs of the studied cases were computed. The total cost for each case was evaluated considering the following building costs: initial cost, repair cost, content loss, income loss, and losses due to both injured and deceased people. The main results of the investigation indicate that the optimal average values of α that minimize the building total cost are: For firm soil: α ¯ OPT = 0.85 for Q = 2 and α ¯ OPT = 0.94 for Q = 4. For soft soil: α ¯ OPT = 0.22 for both values of Q.